Experimental Study of the Relationship between the Content of Sand in Partially Expansive Clayey Soil and Both Direct Shear and Unconfined Compressive Strength - الزاوي, منذر; عبد الله, صفوان; إبراهيم, جهاد; النمر, عمار (Latakia University Journal -Engineering Sciences Series, 2020)
The mechanical behavior of the expansive clayey soil affects by the adding percentage of sand due to the different components of both the coarse part (sand) and the fine part (clay) which control the cohesion and friction of the soil. Strength properties are also affected by the density and water content of soil. In this research, direct shear and unconfined compressive strength tests were conducted for different percentages of sand with various densities and saturation degrees. It was found that the degree of saturation, dry density and the percentage of sand have a significant effect on the soil strength, the relationship between cohesion and unconfined compressive strength for all percentages of sand was also discussed. The results showed that the optimum percentage of adding sand should not be less than 30% for clayey soils.